Investigation of hydro-mechanical particle flow through horizontal orifices - Qiu, Zhenghui (Department of Civil Engineering, 2018)
In the modern world, as the global population continues to rise, the need for and recovery of natural resources is becoming ever more relevant. Identifying optimisation solutions for the recovery of granular resources has progressed into one of the most dominant development areas in the mining and processing industries. Two relevant examples from these sectors include the offshore extraction of materials from the ocean floor via hydraulic transport and the processing of mineral particulates through chutes, and hoppers. A common feature of recovery employed in such areas is the rate at which these materials pass through an orifice. The orifice is the interface between the implemented collection or transport system and the targeted material source. Extensive research has been done on the gravitational passing of particles through an orifice, where in contrast, limited knowledge exists on alternative driving factors of flow. The movement of particles induced both mechanically and hydraulically formed the basis of this dissertation in which selected granular materials were experimentally characterised. Specifically, the following were studied: the effect of orifice and particle size, changes in system velocity and the effects of suction. The system encompassed a scaled down model of a real-life application. An experimental and numerical analysis approach was undertaken, where the calibration of the simulated model was dependent on the former. A total of 327 experimental tests were conducted on the flow ability of high sphericity (±95% roundness) glass beads. A numerical model based on the physical parameters was calibrated to further assist in the overall analysis of the system. The model was of a discrete element method (DEM) type. Empirically, it was found that the Beverloo law, an expression used to describe the discharge of particles through a hopper, had many aspects that were dimensionally suited for the study. Through certain boundary assumptions made in the study, the law was in agreement with the stated outputs. The ratio (R) between the orifice (Dₒ) and particle diameter (dₚ) had a significant influence on the entrainment rate, where there existed a region (R > 4) of limiting flow. Changes in the system velocity, were found to have a negligible effect on the overall recovery but a direct relationship with the rate at which the material was collected. The introduction of suction improved the recovery of materials greatly, increasing the mass flow rate by more than 300%. The in-depth analysis on a multitude of orifice configurations, considerably extended the understanding of the behaviour of particles passing through an opening, particularly spherical particles under fluid or mechanical driven flow. Results indicated that there was a lot of potential for improving the optimisation of granular flow. Optimisation in this sense was defined as maximising the recovery (%) or collection rate (kg/s) of the system. Boundary conditions and design guidelines were offered to address this issue. Areas where further research could advance this understanding were highlighted.